The Late Permian Kupferschiefer Fossils and the Geological Educational Trail in the UNESCO Global Geopark TERRA.vita (NW Germany) - Tobias Fischer; Lothar Schöllmann; Johannes Haunert (Geoconservation Research)
The iconic Kupferschiefer is a stratigraphic marker horizon of the Upper Permian in Northern and Central Europe, which is recognized internationally as a unique stratum because of its outstanding preservation of fish, reptile, and plant fossils. In the UNESCO Global Geopark TERRA.vita, Kupferschiefer fossils have been found at three tectonically uplifted elevations: Hüggel, Schafberg, and Piesberg. Here we review not only the Kupferschiefer fossil record of the Geopark, but also the paleontological excavations and environmental education programs that have been undertaken by the LWL Museum of Natural History in Münster, the local associations Museumsverein Hüggel e.V. and Kultur- und Verkehrsverein Hasbergen e.V. in Hasbergen, and the UNESCO Global Geopark TERRA.vita over the past 40 years. Particular emphasis is placed on the Hüggel hill, where the TERRA.track Geological Educational Trail has been set up to explain to visitors the high geodiversity and centuries-long mining history of the area. Furthermore, we provide comments on the future of the Geocenter in Hasbergen, where the Kupferschiefer fossils from Hüggel have been exhibited until 2018.